The Influence of Online Shopping Convenience and Consumer Trust on Online Purchasing Decisions in Medan City Society - Zebua, Adiwima; Asyari, Abdur Rahman; Lbn. Raja, Edward Alezandro; B. Sinaga, Endang; Hasugian, Putra Tunggal; Lbn. Raja, Dhea Rebeca (Universitas Syiah Kuala, 2025)
This study was conducted based on a phenomenon, namely why consumers want to buy products online even though this system has several risks such as fraud by sellers, the length of time for goods to arrive and others. The purpose of this study was to determine the effect of ease of online shopping and consumer trust on online purchasing decisions in the Medan City community. This study uses a quantitative approach by collecting data through a survey method. The population used in this study were consumers who had shopped online in Medan City. This study uses a non-probability sampling technique with a stratified random sampling approach or sampling based on stratification. The sample in this study was 100 people based on the Household Analysis Unit taken from 3 sub-districts in Medan City. The data collection technique used a questionnaire that had been tested for validity and reliability. The data analysis technique used to answer the hypothesis was multiple regression. The results of this study indicate that Ease of Online Shopping has a positive and significant effect on Online Purchasing Decisions, as evidenced by the t-count value of 7.541 with a significance value of 0.000 and the regression coefficient has a positive value of 0.749. Consumer Trust has a positive and significant effect on Online Purchasing Decisions as evidenced by the t-value of 3.759 with a significance value of 0.000 and the regression coefficient has a positive value of 0.499. Ease of Online Shopping and Consumer Trust have a positive and significant effect on Online Purchasing Decisions as evidenced by the F-value of 79.765 with a significance of 0.000. The R Square value of 0.622 indicates that the ability of the independent variable to explain the variation of the dependent variable is 62.2%, and the remaining 37.8% is explained by other variables outside the research model.